Rancang Bangun Website Layanan Pendidikan Guna Mendukung Administrasi dan Branding di TKIT Al Binaa - Aditya Daffa Syahputra; Risma, Risma Auliya Salsabilla; Afridho, Afridho Ikhsan; Ananta, Ananta Ziaurohman Az Zaki; Maheswara, Maheswara Abhista Hamdan Hafiz; Ari, Ari Rizwan; Alfia, Alfia Meilani Putri; Johan; Garno, Garno (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Easy and accurate access to information about TKIT Al Binaa is a crucial need for the community, particularly for parents who require detailed information on educational services. The limited time parents have to conduct direct surveys necessitates a medium that can effectively provide this information. This article proposes the development of a website to support information management, administration, and branding at TKIT Al Binaa. The website is expected to ease public access to necessary information while assisting the school in disseminating information and facilitating administrative processes efficiently. The website development follows four main stages: data collection, website creation, usage socialization, and evaluation. Data were collected through observation, interviews, and PIECES analysis to meet the school's needs. This initiative is anticipated to significantly contribute to resolving information access issues and reinforce TKIT Al Binaa's brand as a technologically-oriented institution. Throughout the program, the school has shown high enthusiasm and welcomed the outcomes of this initiative.